Mitochondrial calcium uniporter Mcu controls excitotoxicity and is transcriptionally repressed by neuroprotective nuclear calcium signals - Qiu, Jing; Tan, Yan-Wei; Hertle, Anna M.; Martel, Marc-Andre; Kneisel, Niclas; Skehel, Paul A.; Wyllie, David J. A.; Bading, Hilmar; Hardingham, Giles E. (Nature Communications, 2013)
The recent identification of the mitochondrial Ca2+ uniporter gene (Mcu/Ccdc109a) has enabled us to address its role, and that of mitochondrial Ca2+ uptake, in neuronal excitotoxicity. Here we show that exogenously expressed Mcu is mitochondrially localized and increases mitochondrial Ca2+ levels following NMDA receptor activation, leading to increased mitochondrial membrane depolarization and excitotoxic cell death. Knockdown of endogenous Mcu expression reduces NMDA-induced increases in mitochondrial Ca2+, resulting in lower levels of mitochondrial depolarization and resistance to excitotoxicity. Mcu is subject to dynamic regulation as part of an activity-dependent adaptive mechanism that limits mitochondrial Ca2+ overload when cytoplasmic Ca2+ levels are high. Specifically, synaptic activity transcriptionally represses Mcu, via a mechanism involving the nuclear Ca2+ and CaM kinase-mediated induction of Npas4, resulting in the inhibition of NMDA receptor-induced mitochondrial Ca2+ uptake and preventing excitotoxic death. This establishes Mcu and the pathways regulating its expression as important determinants of excitotoxicity, which may represent therapeutic targets for excitotoxic disorders.
Gesehen am 05.01.2022